2013
DOI: 10.1016/j.resp.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors, immune changes and respiratory diseases in troops during military activities

Abstract: Combat operations in contemporary theaters of war, as well as combat training, are carried out in all parts of the world, typically in a harsh environment. Specific environmental conditions, such as heat, cold, high-altitudes, desert climates, as well as chemical and biological pollution of both the atmosphere and soil, together with over-exertion, food restrictions, sleep deprivation, and psychological stress can all result in changes in the immune system and the occurrence of associated diseases. Respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Long-term exposure to desert dust particles will lead to nonindustrial pneumoconiosis or desert lung syndrome [117]. Currently, studies continue to examine dust and related health effects for troops deployed in desert regions of Iraq and Afghanistan to understand exposure as well as pathogens in the dust [118][119][120][121][122][123][124].…”
Section: Desert Dust and Other Respiratory Diseasesmentioning
confidence: 99%
“…Long-term exposure to desert dust particles will lead to nonindustrial pneumoconiosis or desert lung syndrome [117]. Currently, studies continue to examine dust and related health effects for troops deployed in desert regions of Iraq and Afghanistan to understand exposure as well as pathogens in the dust [118][119][120][121][122][123][124].…”
Section: Desert Dust and Other Respiratory Diseasesmentioning
confidence: 99%
“…The appropriate use of IT instillation for toxicology testing has been addressed by a panel of experts from the Inhalation Specialty Section of the Society of Toxicology that concluded that IT instillation serves a valid mode in hazard identification (Driscoll et al 2000). Second, service personnel in Iraq were exposed not only to field dust, but also to pit burning, spores, and other pollutants (Rose 2012; Korzeniewski et al 2013). In light of the current study, evaluation of coexposure to field dust and particles generated during pit burning is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…There are few quantitative exposure data for military personnel during Operation Iraqi Freedom/Operation Enduring Freedom, and exposures in the military operational environment are complex, involving field dust, pit burning, spores, munition combustion products, diesel exhaust, and various other chemicals (Rose 2012; Korzeniewski et al 2013). Consequently, it has proved challenging to investigate the association of postdeployment respiratory disease with particular exposures or events in SWA.…”
mentioning
confidence: 99%
“…The problem is important from the clinical standpoint since the world seemingly has forgotten about this kind of infections. The theme of respiratory infections is topped by the article of Korzeniewski et al (2013) that describes respiratory illnesses among soldiers deployed in faraway war arenas. The article is valuable taking into account the scarcity of such analyses.…”
Section: Foreword ଝmentioning
confidence: 99%